Features of localization, frequency of occurrence and combination of endometrioid lesions in recurrent external genital endometriosis - F. T. Aliyeva; D. V. Bryunin (Лечащий Врач, 2023)
Endometriosis is a chronic, dyshormonal, immune-dependent disease with a characteristic proliferation of tissue similar in morphological structure to the endometrium and located outside the endometrial mucosa. The goal of investigation was to study the peculiarities of localizations and combinations of endometrioid lesions in recurrent external genital endometriosis. 48 patients with recurrent external genital endometriosis were examined. The average age of the examined was 34.96 ± 1.1 years and ranged from 19 to 50 years. The study of the menstrual function made it confirmed that menarche was observed from 13.8 ± 1.9 years, the duration of the menstrual cycle was within 28.75 ± 0.53 (23-45) days, the duration of menstruation was 5.65 ± 0.17 (3-10) days. The onset of sexual activity in patients was noted from 18.98 ± 0.39 (15-30) years. The duration of endometriosis in patients with recurrent forms of external genital endometriosis was 10.0 ± 1.41 (9-11) years. The recurrence rate averaged 2.02 ± 0.44 (1-4) years. The duration of remission was 6.1 ± 0.84 (1-15) years on average. All patients underwent clinical, functional, endoscopic, immunological and morphological methods of examination. It was found out that recurrent external genital endometriosis in 35.7% of cases is manifested by the relapse of endometrioid ovarian cysts, in 24.6% by the presence of endometrioid infiltrates of the sacro-uterine ligaments, in 10.3% of cases by endometriosis of the pelvic peritoneum, in 7.1% of cases by endometriosis of sacro-uterine ligaments, in 6.3% of the presence of retrocervical endometrioid infiltrate, in 5.6% by ovarian endometriosis, in 4.8% of cases by endometriosis of the vesicouterine fold of the peritoneum. The study of the combination and dissemination of endometrioid lesions in recurrent external genital endometriosis demonstrated the presence of stage II of the pathological process according to the classification by A.I. Ishchenko (1993). At the same time, 27.1% of patients had a combination of endometrioid ovarian cyst and endometrioid infiltrates of the sacro-uterine ligaments, 14.8% endometriosis of the sacro-uterine ligaments, 8.3% of patients had endometriosis of the sacro-uterine ligaments and election of the unilateral ovary.